The effect of music therapy on language communication and social skills in children with autism spectrum disorder: a systematic review and meta-analysis - Shi, Zijuan; Wang, Si; Chen, Maoqing; Hu, Aimin; Long, Qingwen; Lee, Yujun (Frontiers in Psychology, 2024)
Background: Studies have shown that music therapy can be used as a therapeutic aid for clinical disorders. To evaluate the effects of music therapy (MT) on language communication and social skills in children with autism spectrum disorder (ASD), a meta-analysis was performed on eligible studies in this field.Methods: A systematic search was conducted in eight databases: PubMed, Embase, Web of Science, Cochrane Library databases, the China National Knowledge Infrastructure (CNKI), Wanfang Data, the Chinese Biomedical Literature (CBM) Database, and the VIP Chinese Science and Technology Periodicals Database. The standard mean difference (SMD) values were used to evaluate outcomes, and the pooled proportions and SMD with their 95% confidence intervals (CIs) were also calculated.Eighteen randomized controlled trial (RCT) studies were included, with a total of 1,457 children with ASD. This meta-analysis revealed that music therapy improved their language communication [SMD = -1.20; 95%CI -1.45, -0.94; χ²(17)=84.17, I 2 =80%, P<0.001] and social skills [SMD = -1. 13; 95%CI -1.49, -0.78; χ²(17)=162.53, I 2 =90%, P<0.001]. In addition, behavior χ²(13)=235.08, I 2 =95%, P<0.001],sensory perception [SMD = -1.62; 95%CI -2.17, -1.08; χ²(16)=303.80, I 2 =95%, P<0.001], self-help [SMD = -2. 14; 95%CI -3.17, -1.10; χ²(6)=173.07, I 2 =97%, P<0.001] were all improved.Music therapy has a positive effect on the improvement of symptoms in children with ASD.